THE ROLES OF RURAL INSTITUTIONS ON FOOD SECURITY POLICY IN EAST JAVA PROVINCE INDONESIA - Nuhfil Hanani; Rosihan Asmara; Fahriyah Fahriyah; Sujarwo Sujarwo (Agricultural Socio-Economics Journal, 2016)
This study has two main objectives, which are to identify rural institutions and their roles for supporting the implementation of food security policy in East Java Province and to formulate the model of rural institutions to enhance food security in the village level. This study was conducted on February 2012 in six regencies, which represented different food insecurity level in each locations. Primary data were collected by participatory rural appraisal method involving administrators of rural institutions. Descriptive analysis is used to describe rural institutions and their roles on food security implementation. Gap analysis is used to formulate the model to increase the roles of institutions on food security policy. It can be concluded that there are six potential rural institutions supporting food security in village level, which are women farmers’ group, farmers’ group, farmers’ group association, family welfare institution (PKK), rural cooperative, and food barn institution. Farmers’ group, farmers’ group association, and food barn institution potentially support food availability. Meanwhile, on accessibility aspect, farmers’ group, farmers’ group association, rural cooperative, and food barn institutions provide sufficient strength on this role. The last aspect on food security is food utilization. This aspect will be well supported by family welfare institution (PKK) and women farmers’ group. Finally, the institutional form in the village level fostering all aspect of food security is rural food team or TPD (Tim Pangan Desa).